Native tropical timber resource use in the community of Emilio Rabasa, at the Selva El Ocote Biosphere Reserve in Chiapas, Mexico - Orantes-García, Carolina; Pérez-Farrera, Miguel Ángel; Carpio-Penagos, Carlos Uriel; Tejeda-Cruz, César (Instituto de Ecología, A.C., 2013)
This study aimed to identify the use of native tropical timber resources in the Emilio Rabasa community located in the Ocote Forest Biosphere Reserve, in Chiapas state, Mexico. 30 semi-structured surveys were conducted with ejidatarios “land-owners”, and several specimens were collected for their identification. A total of 35 native timber species were determined, included in 31 genera and 24 families.The main multipurpose timber species mentioned were bojón (Cordia alliodora (R. & P.) Oken), palo amarillo (Terminalia obovata (R. & P.) Steud), mahogany (Swietenia macrophylla G. King), the jolocín (Heliocarpus donnell-smithii Rose), cedar (Cedrela odorata M. Roem. King) and copalchi (Croton guatemalensis Lotsy). Among the main uses that the community gives these timber species are 38% for extraction of firewood and fence posts, 17% for making tools and 16% for making furniture, construction and houses repair.